A Comparative / Contrastive Study of Prepositional Phrases and Noun Phrases In the English and Arabic Languages - Shaima; Hussein al-Mi’mar, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Syntax is a branch of linguistics that deals with the arrangement of words in a sentence and the structure of a sentence in a language and how the various parts of sentence go together. A preposition in syntax is a word which cannot occur alone. It joins a noun or pronoun to another word to indicate some relation between the words in a phrase or in a sentence. A noun phrase on the other hand may be viewed as having potentially three parts: Pre-modification – noun – post modification. The present study is a comparison between English and Arabic prepositional phrases and noun phrases. It attempts to find whether prepositional phrases and noun phrases in Arabic, is similar to that of English or not. The study aims at: 1. Conducting a theoretical study of prepositional phrases and noun phrases. 2. Analyzing a representative sample of Arabic and English prepositional phrases and noun phrases.3. Conducting a comparative study based on the results of the analysis as carried out above. 4. Drawing relevant conclusions. The paper is hoped that the results of this study will throw valuable light on prepositional phrases and noun phrases in the two languages.